1984
DOI: 10.1093/nar/12.6.2669
|View full text |Cite
|
Sign up to set email alerts
|

Non-Alu family interspersed repeats in human DNA and their transcriptional activity

Abstract: Randomly selected human genomic clones have been surveyed for the presence of non-Alu family interspersed repeats. Four such families of repeats have been isolated and characterized with respect to repetition frequency, interspersion, base sequence, sequence divergence, in vitro RNA polymerase III transcription, elongation of transcripts in isolated nuclei, and in vivo transcription. The two most abundant of the four families of repeats correspond to previously reported families of repeats, namely the kpn I fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

1985
1985
1996
1996

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(39 citation statements)
references
References 43 publications
2
37
0
Order By: Relevance
“…An alignment of the sequences surrounding the recombination points is compared to the sequence of the HeLa 5R circle in Fig. 6 (2,3,11,13,14). A variety of characteristics including the presence of an A-rich 3' tail and variably sized target site duplications have led to the classification of Alu and L-1 sequences as retroposons.…”
Section: Resultsmentioning
confidence: 99%
“…An alignment of the sequences surrounding the recombination points is compared to the sequence of the HeLa 5R circle in Fig. 6 (2,3,11,13,14). A variety of characteristics including the presence of an A-rich 3' tail and variably sized target site duplications have led to the classification of Alu and L-1 sequences as retroposons.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to Alu and L1 sequences, O-family repetitive sequences (Sun et al, 1984) were found at the position between 1076 and 1418. The O-family repeat is flanked by 6 bp TSDs.…”
Section: Sequence Of Clone Plmentioning
confidence: 99%
“…In addition to these SINES and LINES, retrovirus-like repetitive sequences have been identified. The O-family sequence is one such repetitive sequence and is considered to be a solitary LTR (long terminal repeat) (Sun et al, 1984;Paulson et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…This group of elements, designated THE 1 repeats by Sun et al [62], was isolated from a human DNA library as clones hybridizing to human genomic DNA but not to an Alu family member. Like the other endogenous retroviral sequences discussed here, these elements possess features indicative of having been generated by the reverse flow of genetic information from RNA to DNA.…”
Section: B Identification and Isolation Of Human Endogenous Retrovirmentioning
confidence: 99%